Promoting the health and wellbeing of teenage mothers in Mopani District Limpopo Province - Peu, Mmapheko Doriccah (University of Pretoria, 2018)
Health promotion in rural villages provides an important opportunity for registered nurses not only to address the curative and preventive side of healthcare, but also the wellbeing of teenage mothers to ensure their continued development and education. The Limpopo Provincial Government indicates significantly high rates of unwanted pregnancies among unmarried teenage girls from as young as 10 and 11 years due to lack of knowledge about sexuality, contraceptives, negative attitudes of staff, poverty and family breakdown. The researcher observed that once they are teenage mothers, the majority did not return to school to complete their education. She was concerned about the dismal future faced by so many young girls whose human rights, autonomous decision making and the privilege of having a childhood life were forcefully taken away from them through early motherhood. This became the driving force for the researcher to obtain empirical evidence confirming there is an urgent need to promote the health and wellbeing of teenage mothers in the Mopani District, Limpopo, South Africa. The aim of the study was to develop guidelines to promote the health and wellbeing of teenage mothers in rural villages in the Mopani District in Limpopo. This study comprised of 2 phases. The specific objectives of Phase 1 were to explore and describe challenges experienced by registered nurses regarding the promotion of health and wellbeing of teenage mothers and to describe barriers experienced by teenage mothers in returning to school post-delivery. In the first phase, a qualitative study Data analysis was conducted according to Tesch‘s method (in Creswell 2009:186) as described below. In the first phase, a qualitative study rooted in the conceptual revised health promotion model of Pender was done with 15 registered nurses and 15 teenage mothers in two of the poorest villages in Mopani District. The data obtained from this empirical phase was transcribed verbatim by the researcher in consultation with an independent coder which led to the seven themes that emerged. The results of phase 1 of the study displayed challenges of health care service provision by registered nurses, during antenatal, labour, and post-natal care including follow up. Lack of support for child care and need for child support grant was exhibited. Post-natal barriers to access contraceptives and to return to school were shown. However, a plan of action was also suggested by participants. A literature control verified the findings in context. The conclusions drawn from the findings of the empirical phase were used to draft a set of preliminary guidelines for promoting the health and wellbeing of teenage mothers including their return to school in Mopani District. In the second phase, the integration of study findings in relation to Pender‘s model formed the basis which guided the formulation and development of drafting preliminary guidelines. The specific objective of Phase 2 was to develop guidelines to promote the health and wellbeing of teenage mothers in rural villages in Mopani District, Limpopo. In this phase, the Delphi technique was employed, utilising purposefully selected experts from different disciplines and different provinces who had experience in health promotion among teenage girls and teenage mothers. Consensus was reached among the experts and the development of seven guidelines for promoting the health and wellbeing of teenage mothers in the selected setting and in other rural settings was done as well. The guidelines developed could be the resources for promoting teenagers‘ health and wellbeing, their interaction and integration with families, schools and communities, and achievement of the development goals of the province and the country as well as contribute to knowledge and education through curriculum development in Nursing Science. If the situation fails to change, school drop-out will not decline. On the other hand, registered nurses can and should follow a health promotion strategy that supports healthy teenage development that is sensitive to the situation of teenage mothers in rural villages in order to promote their health and wellbeing in a manner that transforms their environment and increases their educational opportunities and life chances. The study objectives were successfully achieved. Ethical considerations and trustworthiness were adhered to throughout the study process. A pilot study was conducted before each phase to validate instruments used. It was recommended that a review of the seven guidelines be done on a regular basis to ensure that they reflect current decisions and are continuously aligned to policies to enhance the health and wellbeing of young teenage mothers and to motivate them to attend school to ensure they have a better future as women and as mothers.